Belimumab in systemic lupus erythematosus - Ankita Srivastava (Wolters Kluwer Medknow Publications, 2016)
Belimumab is the only approved biological agent for the treatment of systemic lupus erythematosus (SLE). It is a fully humanized IgG1γ monoclonal antibody directed against soluble B lymphocyte stimulator (BLyS). It is indicated as an add-on therapy for the treatment of adult patients with active, autoantibody-positive SLE, who are receiving standard therapy. Belimumab is generally well-tolerated, common adverse effects include infections, infusion reactions, hypersensitivity, headache, nausea, and fatigue. Psychiatric events including suicidal tendency, progressive multifocal leukoencephalopathy and malignancies too have been reported. Apart from SLE, the drug is also being tried for other autoimmune disorders.